1992
DOI: 10.1080/03079459208418820
|View full text |Cite
|
Sign up to set email alerts
|

Rapid diagnosis of infectious laryngotracheitis using a monoclonal antibody‐based immunoperoxidase procedure

Abstract: SUMMARYAn indirect immunoperoxidase (IP) procedure using monoclonal antibody was developed for detection of infectious laryngotracheitis (ILT) virus antigen in frozen tissue sections. This IP procedure was compared with an indirect immunofluorescent antibody (FA) procedure, histopathology and virus isolation for detection of ILT virus in tracheas of experimentally infected chickens. Compared with virus isolation, sensitivity and specificity of IP were 72 and 93%, respectively; sensitivity and specificity of FA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
6

Year Published

2007
2007
2019
2019

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 17 publications
(23 reference statements)
1
34
0
6
Order By: Relevance
“…On the other hand, FA test was found to be as reliable as histopathological methods [18] . However, it needs for fluorescence microscopy has been reported as a negative aspect [9] . Williams et al [19] compared virus isolation, electron microscopy, and PCR methods and they found that most sensitive methods were PCR, virus isolation and electron microscopy, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…On the other hand, FA test was found to be as reliable as histopathological methods [18] . However, it needs for fluorescence microscopy has been reported as a negative aspect [9] . Williams et al [19] compared virus isolation, electron microscopy, and PCR methods and they found that most sensitive methods were PCR, virus isolation and electron microscopy, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In an experimental study, immunopositive stainings were observed in laryngeal and tracheal tissues, especially in the cytoplasm of epithelial desquamated and unciliated cells such as goblet cells and mucous gland epithelia [36] . Guy et al [9] reported that in their experimental study, they found positive reactions in tracheal mucosal epithelia and desquamated epithelial cells. In this study, immunopositive reactions were observed in the larynx and tracheal epithelium, luminal epithelial cells and gland epithelium.…”
Section: +5 (Very Serious) Lesions the Epithelial Layer Is Completelmentioning
confidence: 99%
See 2 more Smart Citations
“…Lymphocytes, histiocytic, and blood cells migrate into the mucosa and submucosa in 2-3 days (Garcia et al, 2014). Intranuclear inclusion bodies in the tracheal and conjunctival epithelial cells are present for a few days (1-5 dpi) in the early stages of infection, and then disappear due to necrosis and sloughing of the epithelium (Guy et al, 1992).…”
Section: Epidemiology Of Avian Infectious Laryngotracheitis With Specmentioning
confidence: 99%